Global Connections : politics, exchange, and social life in world history. Volume 1 - Coatsworth, John H., 1940- (Cambridge : Cambridge University Press, 2015)
The first textbook to present world history via social history, drawing on social science methods and research. This interdisciplinary, comprehensive and comparative textbook is authored by distinguished scholars and experienced teachers, and offers expert scholarship on global history that is ideal for undergraduate students. Volume 1 takes us from the origin of hominids to ancient civilizations, the rise of empires, and the Middle Ages. The book pays particular attention to the ways in which ordinary people lived through the great changes of their times, and how everyday experience connects to great political events and the commercial exchanges of an interconnected world. With 65 maps, 45 illustrations, timelines, boxes, and primary source extracts, the book moves students easily from particular historical incidents to broader perspectives, enabling them to use historical material and social science methodologies to analyze the events of the past, present and future.
Title from publisher's bibliographic system (viewed on 24 Sep 2018).
Keywords: elektronické knihy; electronic books; History, Modern; World history